Pengaruh Retensi Pegawai dan Lingkungan Kerja Terhadap Kinerja Pegawai Kecamatan Jekan Raya, Palangka Raya - Rita Yuanita Toendan (Jurnal Manajemen Sains dan Organisasi, 2022)
Abstract Objective - Research in the field of human resource management, aims to provide an empirical explanation of the Effect of Employee Retention and the Work Environment on Employee Performance in Jekan Raya District, Palangka Raya. Design/Methodology/Approach - This research is a quantitative research with a census technique of 35 employees. Questionnaire analysis with SPSS. Research findings – the important role of employee retention and maintaining the work environment in improving the performance of Jekan Raya District employees, in Palangka Raya. These results can be used as input and reference for research sites and similar research sites.